Two treatises of government - Locke, John. (Cambridge Cambridge University Press, 1988)
This is a new revised version of Dr. Laslett's standard edition of Two Treatises. First published in 1960, and based on an analysis of the whole body of Locke's publications, writings, and papers. The Introduction and text have been revised to incorporate references to recent scholarship since the second edition and the bibliography has been updated.
Includes index.
Keywords: Political science --Early works to 1800.